PENERAPAN MODEL MIND MAPPING PADA PEMBELAJARAN IPA UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS V SDN 9 MUARA BATU KABUPATEN ACEH UTARA - Tasnim Idris; Anna Rahmi (FITRAH: International Islamic Education Journal, 2023)
Based on the results of observations and interviews that researchers conducted at SDN 9 Muara Batu class V/a, problems were found related to learning science. The problem found in fifth grade students at SDN 9 Muara Batu, North Aceh District, is that most students have difficulty remembering the material being studied. Especially in science learning there is a lot of material that must be remembered and there are many divisions. Therefore, students need a special learning model that can make it easier for students to remember and record the material being studied. The use of the Mind Mapping model in science learning can be an alternative for teachers and students. The aims of this study are (1) to describe teacher activities in improving student learning outcomes. (2) To describe student activities in improving learning outcomes. (3) To analyze the increase in student learning outcomes by applying the Mind Mapping model to learning science to improve learning outcomes. This research is Classroom Action Research (CAR), with the research subjects being class V/a students totaling 20 students. The individual KKM that has been set is 67 and for classical completeness it is 70%. Data collection techniques were carried out through observation and tests. Observation of teacher activities in managing learning in cycle I obtained a percentage of 80.34% and cycle II to 92.39%. Observation of student activity in cycle I obtained a percentage of 77.17% and cycle II to 89.13%. As for student learning outcomes in cycle I, it obtained a percentage of 55% that had not fulfilled classical completeness and cycle II to 85% had fulfilled classical completeness. So it can be concluded that learning through the application of the Mind Mapping model can improve student learning outcomes.